Interval oscillation criteria for second order forced nonlinear matrix differential equations - Wan-Tong Li; Rong-Kun Zhuang (Electronic Journal of Differential Equations, 2005)
New oscillation criteria are established for the nonlinear matrix differential equations with a forced term $$ [ r(t)Y'(t)] '+p(t)Y'(t)+Q(t)G( Y'(t)) F( Y(t)) =e(t)I_n. $$ Our results extend and improve the recent results of Li and Agarwal for scalar cases. Furthermore, one example that dwell upon the importance of our results is included.